Effects of modified tall oil and vitamin E on growth performance and carcass characteristics of growing-finishing barrows - P R O'Quinn; A T Waylan; J C Woodworth; S I Koo; Jim L Nelssen; John A Unruh; Robert D Goodband; Michael D Tokach (Kansas Agricultural Experiment Station Research Reports, 1999)
A trial was conducted to investigate the interactive effects of modified tall oil (MTO) and vitamin E on growth performance and carcass characteristics of growing-finishing barrows. Feeding MTO resulted in increased ADG and improved F/G during the growing phase; otherwise dietary treatment did not affect growth performance during the rest of the trial or overall. Feeding MTO also decreased backfat thickness and increased belly firmness. Increasing vitamin E in diets containing MTO decreased drip loss percentage of the loin. These results indicate that MTO may function as a growth promoter; reduce backfat; and in conjunction with vitamin E, itnprove some aspects of meat quality.; Swine Day, Manhattan, KS, November 18, 1999
Keywords: Swine day; 1999; Kansas Agricultural Experiment Station contribution; no. 00-103-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 841; Swine; Modified tall oil; Vitamin E; Growth performance; Carcass characteristics